2020
DOI: 10.3389/fphar.2019.01483
|View full text |Cite
|
Sign up to set email alerts
|

Use of Herbal Medicine by Pregnant Women: What Physicians Need to Know

Abstract: About 80% of the consumers worldwide use herbal medicine (HMs) or other natural products. The percentage may vary significantly (7%-55%) among pregnant women, depending upon social status, ethnicity, and cultural traditions. This manuscript discusses the most common HMs used by pregnant women, and the potential interactions of HMs with conventional drugs in some medical conditions that occur during pregnancy (e.g., hypertension, asthma, epilepsy). It also includes an examination of the characteristics of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 154 publications
(220 reference statements)
3
68
0
3
Order By: Relevance
“…100 Finally, successful integration of herbal medicine services requires collaboration between conventional and T&CM clinicians, as well as pharmacists. 101 Herbal medicine education for conventional medicine clinicians and pharmacists are found to be effective in promoting their confidence in communicating with patients about the use of herbal medicines and supplements. 102 , 103 Effective curriculum can be adapted and promoted in Universities across Western Pacific Region.…”
Section: Discussionmentioning
confidence: 99%
“…100 Finally, successful integration of herbal medicine services requires collaboration between conventional and T&CM clinicians, as well as pharmacists. 101 Herbal medicine education for conventional medicine clinicians and pharmacists are found to be effective in promoting their confidence in communicating with patients about the use of herbal medicines and supplements. 102 , 103 Effective curriculum can be adapted and promoted in Universities across Western Pacific Region.…”
Section: Discussionmentioning
confidence: 99%
“…Women are the primary consumers of traditional medicines, and usually continue using them during pregnancy. Pregnant women usually use tradtional medicines as a safe and natural alternative to conventional drugs and often use them to improve their wellbeing or for the treatment of non-life threating conditions (Illamola et al, 2019). However, data on the safety of these herbal treatments during pregnancy are generally insufficient.…”
Section: The Relationship Between Therapeutic Use and Toxicitymentioning
confidence: 99%
“…e prevalence of herbal medicine use by pregnant women ranges between 7% and 79.9% depending on different geographic, social, cultural, and ethnic factors [21,22,25,26]. CHM has a history of about 5000 years, and it has become one of the main therapies in East Asia and has spread to western countries.…”
Section: Chm In Threatened Miscarriagementioning
confidence: 99%
“…e women in the reviewed studies assumed that CAM can promote maternal and fetal health, enhance the efficacy of western medicines, and relieve specific pregnancy-related conditions, but there is poor evidence to support such effects of CAM. In line with this, a series of studies have been performed regarding the safety of CAM for pregnant women [17,[21][22][23]. To date, several studies have reported on women who have had successful pregnancies after threatened miscarriage when being treated with CAM, mainly including Chinese herbal medicine (CHM), acupuncture, nutritional supplements, and psychological interventions [8,10,11,24].…”
Section: Introductionmentioning
confidence: 99%